2020
DOI: 10.3390/biology10010007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Weed Management on the Parasitoid Community in Mediterranean Vineyards

Abstract: Enriching agroecosystems with non-crop vegetation is a popular strategy for conservation biocontrol. In vineyards, the effects of specific seeded or planted cover crops on natural enemies are well-studied, whereas conserving spontaneously developing weeds received less attention. We compared parasitoid communities between matched pairs of vineyard plots in northern Israel, differing in weed management practices: “herbicide”, repeated herbicide applications vs. “ground cover”, maintaining resident weeds and tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…Furthermore, the enhancement of insect biodiversity due to cover plants may play an important role as a natural biological control. Therefore, its use is also recommended as an Integrated Pest Management (IPM) tool to balance and eventually reduces the long-term pest populations increasing the natural enemies' community [62,[66][67][68][69]. Our results showed that within the most abundant genera were Coccinella and Chrysoperla, who are predators of aphids, and Sphaerophoria, who perform both pollination and predation functions.…”
Section: Discussionmentioning
confidence: 81%
“…Furthermore, the enhancement of insect biodiversity due to cover plants may play an important role as a natural biological control. Therefore, its use is also recommended as an Integrated Pest Management (IPM) tool to balance and eventually reduces the long-term pest populations increasing the natural enemies' community [62,[66][67][68][69]. Our results showed that within the most abundant genera were Coccinella and Chrysoperla, who are predators of aphids, and Sphaerophoria, who perform both pollination and predation functions.…”
Section: Discussionmentioning
confidence: 81%
“…The importance of non-crop vegetation or soil cover vegetation for providing resources to parasitoids, such as shelter, overwintering habitat, nectar, pollen, and alternate hosts or preys, have been reported elsewhere by several authors (e.g., Thomson and Hoffmann, 2009; Thomson et al ., 2010; Gaigher et al ., 2015; Smith et al ., 2015; Daane et al ., 2018; Shapira et al ., 2018; Segoli et al ., 2020; Möller et al ., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Failure to follow the GAP code of practice (CoP) had resulted in a high use of chemical pesticides, which had a very significant adverse impact on weed diversity (Aini et al, 2007). According to Möller et al (2021), the abundance of parasitoids was higher in plots with a good ground cover compared to plots treated with herbicides. Wood and Norman (2019b) and Wood et al (1974) also reported that the application of chemicals had consequently disrupted the natural enemies of M. plana in the plantation habitats.…”
Section: P R E S Smentioning
confidence: 99%